Lexico-Grammatical Analysis of Learners' Independent and Integrated Essays in EMI Context - Rahmi, Dery Singkawati; Kweldju, Siusana; Ivone, Francisca Maria (Universitas Tanjungpura, 2025)
A growing number of L2 novice writers in the EMI context lead the present study to examine the learner